IMPROVING QUALITY THROUGH INNOVATIONS: THE ROLE OF VENTURE FINANCING AND HR SUPPORT - Doston T. Turgunov; Bahtiyor Zulfiqor o’g’li G’aniev; Bekzod Sharifjon o’g’li Rahmonov; Ozodbek Alijon o’g’li Suvpulatov; Dilafruz S. Nasirkhodjaeva (International Journal for Quality Research)
We analysed comparative characteristics of the management of quality improvement using innovations with a focus on venture financing and HR support. We revealed leading countries and the specifics of their practices in implementing innovations and studied features peculiar to Canada, Sweden and South Korea. The study of the state, dynamics, and indicators of HR support, venture financing and product quality allowed us to establish the connection and identify the conditions of its absence. The latter is explained by the influence of additional factors, which are certain barriers to the implementation of promising innovative projects in quality improvement. We also established that among the given factors the most negative factor is the insufficient level of equipment modernisation. The goal of this research was to identify the relationship between the improvement of the quality of products (services) and an increase in the use of innovations that are connected with venture financing and HR support. The scientific novelty of this research is due to the determination of the models of improving quality through innovations in the leading countries in the context of venture financing, HR support and high-tech production.